ЛІНГВОДИДАКТИЧНІ ОСОБЛИВОСТІ РОЗВИТКУ ПИСЕМНОГО МОВЛЕННЯ НА УРОКАХ БЛИЗЬКОСПОРЩНЕНОЇ МОВИ (Педагогіка вищої та середньої школи, 2022)
The article deals with lingvodidactic problems of the development of written speech of young pupils at lessons on Ukrainian language learning as a second one.